Mapping personality signaling in Indonesian popular prose: A qualitative content analysis of Ria Ricis’s Bukan Buku Nikah - Kasmantoni Kasmantoni; Vebbi Andra; Fahmy Burniawan (JPI: Jurnal Pustaka Indonesia, 2024)
This study examines how personality is textually constructed in Ria Ricis’s Bukan Buku Nikah and how such construction organizes readers’ moral alignment and narrative engagement. Using a qualitative content analysis (QCA) of the full text, we defined the unit of analysis as discrete utterances or narrated actions that index a stable disposition, developed and iteratively refined a rule-governed codebook, and employed two trained coders who independently coded the corpus before adjudication; intercoder agreement was assessed with Krippendorff’s alpha (α), and an audit trail of codebook versions, memos, and decisions was maintained. Results identified 21 coded instances across eight personality aspects, with good and diligent/industrious each comprising 33% of observations (66% combined), while sympathetic accounted for 9% and five low-frequency categories helpful, dishonest, tenacious, jealous/possessive, and bad each appeared at 5%. Trait distributions clustered by character function: focal figures accumulated prosocial traits, whereas ambivalent cues surfaced briefly as plot catalysts without crystallizing into stable dispositions. These patterns indicate a choreographed “prosocial-effort” profile in which virtue is performed repeatedly in public-facing scenes to stabilize identification, and episodic ambivalence introduces tension that resolves toward didactic clarity. The study contributes a reliability-reported, replicable template for personality-focused literary analysis of Indonesian popular/hybrid prose and clarifies how moral didacticism is structurally distributed at the scene level. Educators can use scene-anchored excerpts to teach actionable social scripts of “performed virtue,” and researchers can align inductive trait maps with standardized personality frameworks and incorporate reader-response measures to test cross-text generalizability and reception effects.